Preparation method of polyester for powder coating

By using hybrid titanium catalysts in the preparation of polyester for powder coatings, the problem of low catalytic efficiency and easy hydrolysis of titanate catalysts under normal pressure is solved, and efficient and stable polyester synthesis is achieved, and the product is clear and transparent.

CN119661821AActive Publication Date: 2025-03-21SHANGHAI HUIYI NEW MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510194285.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

In the prior art, the catalytic efficiency of titanate catalysts under normal pressure is low and easy to hydrolyze, resulting in poor transparency of polyesters for powder coatings.

Method used

Hybrid titanium catalyst (HCEO) is used as a catalyst to improve the catalytic efficiency and avoid hydrolysis by carrying out esterification, acidolysis and pre-polycondensation reaction under normal pressure.

Benefits of technology

The catalytic efficiency of the polyester for powder coatings is significantly improved under normal pressure, the product is clear and transparent, and the catalytic efficiency is increased by 30-50%. The hybrid titanium catalyst has high temperature hydrolysis resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661821A_ABST
    Figure CN119661821A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polyester, and relates to a preparation method of polyester for a powder coating, reaction raw materials are sequentially subjected to esterification reaction, acidolysis reaction and pre-polycondensation reaction under the action of a catalyst, the esterification rate of the esterification reaction is 97-99.5%, the pressure intensity of the esterification reaction is 0.1 MPa, the time of the esterification reaction is 3.5-4.4 h, and the catalyst is a hybrid titanium catalyst; and the mass of the titanium element in the hybrid titanium catalyst is 100-170ppm of the theoretical mass of the polyester for the powder coating. The polyester for the powder coating can be successfully synthesized under normal pressure by selecting the hybrid titanium catalyst, the catalytic efficiency is high, the high-temperature hydrolysis resistance is realized, the stability is high, and the synthesized polyester for the powder coating is excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester and relates to a method for preparing polyester for powder coating. Background Art

[0002] Powder coating is a special coating that uses resin base and curing agent as film-forming substances, supplemented by fillers, pigments and functional additives to form a 100% solid powder form. Compared with traditional coatings, this coating has the following advantages: no VOC (volatile organic compound) emissions, recyclability, energy saving, and good coating performance.

[0003] Powder coatings are mainly divided into two categories: thermoplastic powder coatings and thermosetting powder coatings. However, in the market, thermosetting powder coatings, especially polyester systems, dominate. Polyesters, whether -COOH (carboxyl) or -OH (hydroxyl) functional, can provide coatings with good appearance and mechanical properties, such as toughness and flexibility.

[0004] Polyesters for general-purpose powder coatings have good properties such as weather resistance and moisture resistance. They exhibit good performance in a variety of common application scenarios, different construction conditions and on various coated substrates. Therefore, they are widely used in home appliances, automobiles and auto parts, architectural aluminum profiles, toys and other fields.

[0005] The choice of catalyst plays a vital role in the polyester synthesis process. For the synthesis of powder coating polyester, commonly used catalysts include organotin and titanate. However, organotin catalysts are restricted in use due to the presence of heavy metals. Titanate catalysts, such as tetrabutyl titanate (TBOT) and tetraisopropyl titanate, are widely used, but have low catalytic efficiency under normal pressure. In addition, titanate catalysts are easily hydrolyzed and show instability, which results in poor transparency of the synthesized polyester for powder coating.

[0006] Patent ZL201811008954.1 discloses a polyester resin resistant to high humidity, heat and irradiance, and its preparation method and application. Its raw materials include neopentyl glycol, trimethylolpropane, 2-butyl-2-ethyl-1,3-propanediol, terephthalic acid, adipic acid, and isophthalic acid, and TBOT is used as the catalyst. However, the esterification reaction time is as long as 14.5 hours. The literature (Synthesis and Performance Study of Carboxyl-Terminated Polyester and Semi-Crystalline Polyester for Polyester / Epoxy Powder Coatings [D]. Guangzhou: South China University of Technology, 2010.) uses ethylene glycol, neopentyl glycol, trimethylolpropane, terephthalic acid, isophthalic acid, adipic acid, and acid anhydride to prepare polyester for powder coatings. When TBOT is selected as the catalyst, the esterification reaction time is as long as 12 hours. Both prove that the catalytic efficiency of titanate catalysts at normal pressure is low.

[0007] Therefore, it would be of great significance if a catalyst with high catalytic efficiency and not easy to hydrolyze under normal pressure could be found and applied to the preparation of polyester for powder coating. The application of such a catalyst would bring the following advantages:

[0008] (1) Simplified production operations: No high-voltage equipment is required, which reduces equipment investment and maintenance costs, simplifies the operation process, and improves safety. The simplified equipment structure also reduces the difficulty of operation and safety risks, ensuring the safety of personnel and facilities.

[0009] (2) Excellent product performance: The reaction conditions under normal pressure are mild and easy to control, and polyester with specific structure and performance can be accurately synthesized, thus ensuring the stability of product quality. The synthesized polyester has a regular molecular structure, which gives the coating film good comprehensive properties and further expands the scope of application.

[0010] (3) Effective cost control: Normal pressure reaction reduces energy consumption and energy expenditure, which meets the requirements of sustainable development. At the same time, material volatilization loss is reduced, raw material utilization rate is improved, cost is reduced, and quality fluctuations are reduced.

[0011] (4) Significant environmental benefits: No special high-pressure additives are required, which reduces pollution emissions. The equipment sealing requirements are lowered, reducing the risk of leakage, which is in line with the concept of green chemistry and promotes the sustainable development of the industry. Summary of the invention

[0012] The purpose of the present invention is to solve the problems existing in the prior art, to find a catalyst with high catalytic efficiency and not easy to hydrolyze under normal pressure, and to apply the catalyst to the preparation of polyester for powder coating.

[0013] The premise for the application of polyester for powder coatings is that its esterification rate is high, the pre-condensation product is clear and transparent, and it meets a series of physical properties, such as intrinsic viscosity, number average molecular weight, acid value, etc.

[0014] During the esterification process, the reaction between the acid and the alcohol is initially heterogeneous, that is, the reactants and products are unevenly distributed in the system. However, as the reaction proceeds, especially when the esterification rate exceeds 90%, the acid is able to dissolve in the generated ester, and the reaction turns into a homogeneous reaction, and the system becomes clear. In the early to late stages of the reaction, there is a transition state between the raw materials and the products, which is a key stage in the reaction process.

[0015] The polycondensation process is to remove small molecule alcohols between the generated intermediate esters to form polyesters. In this process, the transition state theory plays an important role. According to this theory, the reactant molecules do not directly form products through simple collisions, but must first pass through a high-energy activated complex (transition state). To reach this transition state, a certain activation energy must be overcome before it can be converted into a product. Activation energy is the minimum energy that the reactant molecules must obtain during the reaction in order to form an activated complex and ultimately convert into a product. Activation energy is usually represented by the symbol Ea, and the unit is joule (J) or kilocalorie / mole (kcal / mol). The size of the activation energy directly affects the reaction rate. The smaller the activation energy, the faster the reaction rate.

[0016] The role of a catalyst in a chemical reaction is to lower the activation energy and make the reaction easier to proceed. It provides a new reaction path with a lower activation energy than the original reaction path. Therefore, more reactant molecules are able to overcome the energy barrier and participate in the reaction, thereby accelerating the reaction rate.

[0017] Under the same reaction system, the lower the activation energy of the catalyst, the higher its catalytic efficiency. In order to compare the activation energies of different catalysts (hybrid titanium catalyst (HCEO), TBOT, tetraisopropyl titanate), the present invention conducted a series of exploratory experiments.

[0018] The steps for preparing polyester for powder coating in the following experiments are roughly the same, the only difference is the type and amount of catalyst. The steps for preparing polyester for powder coating are as follows:

[0019] (a) feeding;

[0020] First, 2-methyl-1,3-propanediol and a catalyst are uniformly mixed to obtain a premix, and then, after preheating a reaction kettle to 100° C., ethylene glycol, terephthalic acid, neopentyl glycol, the premix, trimethylolpropane, and trimethyl phosphate are added thereto;

[0021] (b) esterification reaction;

[0022] After nitrogen or inert gas is introduced to remove the impurities and air in the kettle, the temperature in the kettle is raised to 200°C, and the pressure is maintained at 0.1MPa for 3.5-7.1h. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 95-100°C, and the temperature in the kettle is gradually raised to 260°C at a rate of 4°C / 10min;

[0023] (c) acid hydrolysis reaction;

[0024] After the temperature in the kettle was lowered to 225°C, isophthalic acid was added and reacted for 60 minutes;

[0025] (d) pre-polycondensation reaction;

[0026] Within 20 minutes, the temperature in the kettle was raised to 250°C and the pressure in the kettle was reduced to -101KPa;

[0027] (e) introducing nitrogen or an inert gas to lower the temperature in the autoclave, and cooling the discharged material to obtain polyester for powder coating;

[0028] In steps (a) to (e), the alcohol-acid ratio of the reaction system is 1.1:1; the amount of neopentyl glycol added is 55% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 30% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 1.1:1 of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1 ,3-propylene glycol, ethylene glycol and trimethylolpropane added in an amount of 2% mol; the amount of trimethylolpropane added is 1% mol of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added; the amount of trimethyl phosphate added is 0.3wt% of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added.

[0029] The exploration process is as follows:

[0030] (1) Experiments 1 to 4 were conducted, with the catalyst and dosage being HCEO (100 ppm, i.e., the mass of titanium element in the catalyst is the percentage of the theoretical mass of polyester for powder coating), HCEO (130 ppm), HCEO (150 ppm), and HCEO (170 ppm), respectively;

[0031] The esterification rate x (= actual esterification water output / theoretical esterification water output × 100%) corresponding to experiments 1 to 4 and the reaction time t were plotted into a scatter plot, and the fitting result was Figure 1 The four curves of

[0032] The esterification reaction time (time when the esterification rate reaches 100%) and product state corresponding to experiments 1 to 4 are shown in Table 1;

[0033] Table 1

[0034] Catalyst name Esterification reaction time / min Product status HCEO (150ppm) 206 Clarity and transparency HCEO (170ppm) 230 Clarity and transparency HCEO (130ppm) 256 Clarity and transparency HCEO (100ppm) 264 Clarity and transparency

[0035] From the results, it can be seen that the catalytic efficiency is the fastest when the HCEO dosage is 150ppm;

[0036] (2) Experiments 5 to 8 were conducted, with the catalysts and dosages being HCEO (150 ppm), TBOT (150 ppm), tetraisopropyl titanate (150 ppm), and TBOT (100 ppm), respectively;

[0037] The esterification rate x (= actual esterification water output / theoretical esterification water output × 100%) corresponding to experiments 5 to 8 and the reaction time t were plotted into a scatter plot, and the fitting result was Figure 2 The four curves of

[0038] Get Figure 2 The temperature T in the kettle corresponding to each scattered point in the four curves;

[0039] Respectively Figure 2 The four curves are processed (first-order derivative is substituted into reaction time t) to obtain the slope K (representing the reaction rate constant) of each curve at each scattered point;

[0040] The lnK and T corresponding to Experiments 5 to 8 are -1 Draw a scatter plot and get Figure 3 According to the Arrhenius formula, the slopes of the four straight lines are the four -E a / R, R is the molar gas constant, according to the four-E a / R and R can be calculated to get four E a , as shown in Table 2:

[0041] Table 2

[0042] Catalyst name <![CDATA[Activation energy E a / (kJ·mol -1 )]]> Esterification reaction time / min state HCEO (150ppm) 131.1 206 Clarity and transparency TBOT (150ppm) 338.15 305 opaque Tetraisopropyl titanate (150ppm) 470.65 360 Not clear and not transparent TBOT (100ppm) 340.26 427 Clarity and transparency

[0043] From the results, we can see that when comparing the esterification kinetics of several titanium-based catalysts, we found that the activation energy change trend of these catalysts is consistent with the change trend of the esterification reaction time. Among them, HCEO has the smallest activation energy and the shortest esterification reaction time, so its catalytic efficiency is higher than TBOT, and the improvement can reach 30%-50%. In addition, HCEO can also successfully synthesize polyester for powder coatings under normal pressure, and the product is clear and transparent. However, TBOT will participate in the reaction during the esterification reaction stage, resulting in unstable top temperature, and the temperature fluctuation range is between 80-100°C. With the increase of TBOT dosage, the transparency of the synthesized polyester for powder coatings gradually decreases. When the dosage of TBOT reaches 150ppm, the transparency of the product has become very poor. In addition, when tetraisopropyl titanate catalyzes the esterification reaction, although the top temperature is stable at around 80°C, no water molecules are produced, indicating that the esterification reaction is incomplete, so it cannot be applied to this formula and related fields.

[0044] The above research experiments show that the catalytic efficiency of HCEO is better than that of other catalysts. Therefore, the present invention attempts to use HCEO to prepare polyester for powder coatings. The technical solution of the present invention is as follows:

[0045] A method for preparing polyester for powder coatings, wherein the reaction raw materials are subjected to esterification reaction, acidolysis reaction and pre-polycondensation reaction in sequence under the action of a catalyst, the esterification rate of the esterification reaction is 97-99.5%, the pressure of the esterification reaction is 0.1 MPa, the time of the esterification reaction is 3.5-4.4 hours, the catalyst is a hybrid titanium catalyst, and the structural formula is as follows:

[0046] ;

[0047] The mass of titanium element in the hybrid titanium catalyst is 100-170ppm of the theoretical mass of polyester for powder coating. If the amount of the hybrid titanium catalyst is too low, the effect is not obvious, while if it is too high, it will lead to a decrease in esterification rate and reaction rate.

[0048] Although the hybrid titanium catalyst used in the present invention is a substance that has been disclosed in the prior art, the prior art only uses it as a polycondensation catalyst for the preparation of ordinary PET and PETG, and the polycondensation process is carried out under negative pressure. The working principle of the hybrid titanium catalyst is: in the polyester polycondensation reaction, the titanium atom first undergoes an exchange reaction with the terminal hydroxyl group of the oligomer to generate a metal alkoxide, and the oxygen in the hydroxyethyl ester group in the other molecule attacks the carbonyl carbon atom. The nucleophilic attack of the ester carbonyl oxygen on the central titanium atom increases the positive charge of the carbonyl carbon, thereby increasing the reaction rate.

[0049] The present invention uses it as an esterification catalyst for the first time to prepare polyester for powder coatings. The esterification process is carried out under normal pressure. The working principle of the hybrid titanium catalyst is: the titanium atom can introduce the acid center. In the esterification reaction of terephthalic acid and ethylene glycol, the catalyst provides protons to protonate the carboxyl group of terephthalic acid and the hydroxyl group of ethylene glycol to form a better electrophilic reagent, thereby accelerating the reaction between the two to form an ester bond.

[0050] The present invention unexpectedly found that in the esterification process of preparing polyester for powder coating, the catalytic efficiency of hybrid titanium catalyst is significantly better than that of traditional titanate catalyst.

[0051] As the preferred technical solution:

[0052] In the method for preparing the polyester for powder coating as described above, the reaction raw materials include terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol, and trimethylolpropane.

[0053] The multifunctional structure of 2-methyl-1,3-propanediol can adjust the structure of polyester molecular chain. By changing the molecular structure of polyester, the synthesized polyester has better flexibility. Compared with the use of traditional diols such as 1,4-butanediol, it can reduce the regularity of polyester molecular chain, thereby reducing crystallinity, avoiding problems such as agglomeration of powder coatings during storage due to excessive crystallinity; at the same time, the use of 2-methyl-1,3-propanediol to synthesize polyester helps to improve the weather resistance of powder coatings. In outdoor environments, powder coatings made of polyester modified with 2-methyl-1,3-propanediol can resist erosion by ultraviolet rays, moisture and other factors, and the coating is not easy to powderize or fade, which prolongs the service life of the coating; it can also improve the leveling of powder coatings, make the coating surface smoother, reduce surface defects, and improve the appearance quality.

[0054] In the preparation method of polyester for powder coating as described above, the alcohol-acid ratio of the reaction system is 1.1-1.2:1; the amount of neopentyl glycol added is 50-60% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 20-30% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 2-3% mol of the total amount of reaction raw materials added; and the amount of trimethylolpropane added is 1-2% mol of the total amount of reaction raw materials added.

[0055] In the method for preparing polyester for powder coating as described above, the reaction system also contains a stabilizer (trimethyl phosphate). Adding the stabilizer can inhibit oxidation reaction and reduce the occurrence of oxidative yellowing to a certain extent. The amount of the stabilizer added is 0.3-0.5wt% of the total amount of the reaction raw materials added.

[0056] The preparation method of the polyester for powder coating as described above comprises the following specific steps:

[0057] (a) feeding;

[0058] After preheating the reaction kettle, ethylene glycol, terephthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, trimethylolpropane, a hybrid titanium catalyst, and a stabilizer are added thereto;

[0059] (b) esterification reaction;

[0060] After nitrogen or inert gas is introduced to remove the impurities and air in the kettle, the temperature in the kettle is raised to 190-200°C and the reaction is started. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 95-105°C, and the temperature in the kettle is gradually raised to 245-260°C at a rate of 4°C / 10min;

[0061] (c) acid hydrolysis reaction;

[0062] After the temperature in the kettle is lowered to 220-230°C, isophthalic acid (as an acidolysis agent) is added and reacted for 60-90 minutes;

[0063] During the acid hydrolysis process, a capping reaction occurs to form a polyester resin mainly composed of terminal carboxyl groups. The reaction equation is as follows:

[0064] ;

[0065] (d) pre-polycondensation reaction;

[0066] Raise the temperature in the kettle to 220-250°C within 20-30 minutes and reduce the pressure in the kettle to -101KPa;

[0067] The purpose of the prior art pre-condensation is to make the monomers initially polymerize to form a pre-polymer with a higher molecular weight, which generally lasts for a longer time and optimizes the molecular weight distribution. Different from the prior art, the purpose of the pre-condensation of the present invention is to extract the small molecules remaining in the system to further increase the molecular weight of the product. Therefore, the temperature of the pre-condensation reaction of the present invention is lower and the time is shorter, so that the side reactions can be reduced while avoiding the explosion, and the polyester for powder coating with the required molecular weight and viscosity can be obtained;

[0068] (e) After nitrogen or inert gas is introduced to lower the temperature in the autoclave, the material is discharged into a mold and cooled to obtain polyester for powder coating.

[0069] In the method for preparing polyester for powder coating as described above, in step (a), the preheating temperature is 80-100°C, and before feeding, 2-methyl-1,3-propanediol and the hybrid titanium catalyst are first mixed evenly, so that feeding can be convenient.

[0070] The method for preparing the polyester for powder coating as described above has a number average molecular weight of 4000-4800 g / mol, an intrinsic viscosity of 0.13-0.14 dL / g, an acid value of 18-20 mKOH / g, a glass transition temperature (Tg) of 60-62°C, and is clear and transparent.

[0071] Principle of the invention:

[0072] The reason why traditional titanate catalysts have low catalytic efficiency and are easy to hydrolyze at normal pressure is that the titanium atom in the titanate catalyst is connected to the alkoxy group through a covalent bond, forming a Ti-O bond with a certain polarity. This polarity makes the Ti-O bond vulnerable to attack by nucleophiles. Under normal pressure conditions, the water molecules generated in the reactor act as nucleophiles, and the lone pair of electrons on their oxygen atoms will be attracted by the positively charged titanium atoms in the Ti-O bond, thereby triggering a hydrolysis reaction and generating solid impurity particles such as titanium dioxide. These impurity particles not only affect the physical and chemical properties of the polymer, but may also lead to a series of problems such as increased oligomer content and yellowing of the color. In addition, titanate compounds themselves have high chemical activity and are easy to react with substances containing active hydrogen. Since water is a typical substance containing active hydrogen, it can easily react chemically with titanate, resulting in the hydrolysis of titanate. Reasons for low catalytic efficiency: (1) Reduction of active sites: Hydrolysis destroys the chemical bonds and active site structure of titanate, resulting in a significant reduction in the number of active sites; hydrolysis products such as titanium dioxide are deposited on the catalyst surface, covering the active sites and hindering the contact of reactants. (2) Changes in chemical structure: Hydrolysis destroys the coordination environment of titanium atoms, causing them to lose their original electronic structure and spatial configuration, changing catalytic activity and selectivity; hydrolysis converts titanate into inactive or low-activity substances, which cannot effectively reduce the activation energy of the reaction. (3) Reduction in specific surface area: Hydrolysis causes particle agglomeration, resulting in a decrease in the specific surface area of ​​the catalyst and a decrease in the contact area between the reactants and the catalyst.

[0073] The present invention uses a green and hydrolysis-resistant hybrid titanium catalyst to synthesize polyester for powder coatings, and has high catalytic efficiency and stable reaction, because: (1) the hybrid titanium catalyst has an original nano-sheet structure and hybrid composition, which makes the molecular interaction strong, endows the catalyst with excellent hydrolysis resistance, can participate in esterification reaction, and has stable structure and performance; (2) the hybrid titanium catalyst has a fragment similar to terephthalic acid and a fragment similar to diol, and these two fragments can respectively produce strong interactions with the reactants terephthalic acid and diol, thereby attracting the two to gather and collide at the catalyst, thereby promoting the esterification reaction. In addition, due to the presence of a chain segment similar to diol, the catalyst can be well dispersed in diol, and further uniformly dispersed in the esterification system, greatly increasing the collision probability of terephthalic acid and diol near the catalyst, so the hybrid titanium catalyst has good catalytic activity.

[0074] Beneficial effects:

[0075] The present invention uses an environmentally friendly and hydrolysis-resistant hybrid titanium catalyst to synthesize polyester for powder coatings. The hybrid titanium catalyst can successfully synthesize polyester for powder coatings under normal pressure and has a high catalytic efficiency. The catalytic efficiency can be increased by 30-50% compared with traditional titanate catalysts. In addition, the catalyst is resistant to high-temperature hydrolysis and has strong stability. The synthesized polyester for powder coatings is clear and transparent. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 It is a curve diagram showing the relationship between the esterification rate and the reaction time under different dosages of hybrid titanium catalyst;

[0077] Figure 2 It is a curve diagram showing the relationship between esterification rate and reaction time under different catalysts and dosages;

[0078] Figure 3 lnK and T under different catalysts and dosages -1 relationship diagram. DETAILED DESCRIPTION

[0079] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0080] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0081] Number average molecular weight: tested by room temperature gel chromatography (PL-GPC50, Agilent, USA), the solvent was hexafluoroisopropanol, and the concentration of the prepared solution was 1 mg / mL.

[0082] Intrinsic viscosity, acid value: According to GB / T 14190-2017 "Test method for fiber-grade polyester (PET) chips", the intrinsic viscosity and acid value of the sample to be tested are tested.

[0083] Glass transition temperature: The test was carried out using a Q20 high-temperature TA scanning calorimeter in a nitrogen atmosphere. The initial temperature was set at 30°C, kept warm for 1 min, then heated to 300°C at a rate of 15°C / min, kept warm for 5 min, then cooled to 30°C at a rate of 15°C / min, kept warm for 5 min, and finally heated to 300°C at a rate of 15°C / min.

[0084] Example 1

[0085] A method for preparing polyester for powder coating, the specific steps are as follows:

[0086] (a) feeding;

[0087] First, 2-methyl-1,3-propanediol and a hybrid titanium catalyst (manufacturer: Shanghai Huiyi New Material Technology Co., Ltd., model: HCEO) were uniformly mixed to obtain a premix, and then the reactor was preheated to 80°C, and ethylene glycol, terephthalic acid, neopentyl glycol, the premix, trimethylolpropane, and trimethyl phosphate were added thereto;

[0088] (b) esterification reaction;

[0089] After nitrogen or inert gas is introduced to remove the impurity air in the kettle, the temperature in the kettle is raised to 200°C, and the pressure is maintained at 0.1MPa for 4.4h. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 95°C, and the temperature in the kettle is gradually raised to 260°C at a rate of 4°C / 10min;

[0090] The esterification rate of the esterification reaction was 97%;

[0091] (c) acid hydrolysis reaction;

[0092] After the temperature in the kettle was lowered to 230°C, isophthalic acid was added and reacted for 90 minutes;

[0093] (d) pre-polycondensation reaction;

[0094] Within 20 minutes, the temperature in the kettle was raised to 250°C and the pressure in the kettle was reduced to -101KPa;

[0095] (e) introducing nitrogen or an inert gas to lower the temperature in the autoclave, and cooling the discharged material to obtain polyester for powder coating;

[0096] In steps (a) to (e), the mass of titanium element in the hybrid titanium catalyst is 100 ppm of the theoretical mass of polyester for powder coating; the alcohol-acid ratio of the reaction system is 1.1:1; the amount of neopentyl glycol added is 50% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 30% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 100 ppm of terephthalic acid, The amount of trimethylolpropane added is 2% mol of the total amount of isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added; the amount of trimethylolpropane added is 2% mol of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added; the amount of trimethyl phosphate added is 0.3wt% of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added.

[0097] The final polyester for powder coating has a number average molecular weight of 4000 g / mol, an intrinsic viscosity of 0.13 dL / g, an acid value of 18 mKOH / g, a glass transition temperature of 60° C., and is clear and transparent.

[0098] Example 2

[0099] A method for preparing polyester for powder coating, the specific steps are as follows:

[0100] (a) feeding;

[0101] First, 2-methyl-1,3-propanediol and a hybrid titanium catalyst (manufacturer: Shanghai Huiyi New Material Technology Co., Ltd., model: HCEO) were uniformly mixed to obtain a premix, and then the reactor was preheated to 90°C, and ethylene glycol, terephthalic acid, neopentyl glycol, the premix, trimethylolpropane, and trimethyl phosphate were added thereto;

[0102] (b) esterification reaction;

[0103] After nitrogen or inert gas is introduced to remove the impurity air in the kettle, the temperature in the kettle is raised to 195°C, and the pressure is maintained at 0.1MPa for 4.27h. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 100°C, and the temperature in the kettle is gradually raised to 255°C at a rate of 4°C / 10min;

[0104] The esterification rate of the esterification reaction was 98%;

[0105] (c) acid hydrolysis reaction;

[0106] After the temperature in the kettle was lowered to 225°C, isophthalic acid was added and reacted for 70 minutes;

[0107] (d) pre-polycondensation reaction;

[0108] Within 30 minutes, the temperature in the kettle was raised to 240°C and the pressure in the kettle was reduced to -101KPa;

[0109] (e) introducing nitrogen or an inert gas to lower the temperature in the autoclave, and cooling the discharged material to obtain polyester for powder coating;

[0110] In steps (a) to (e), the mass of titanium element in the hybrid titanium catalyst is 130 ppm of the theoretical mass of polyester for powder coating; the alcohol-acid ratio of the reaction system is 1.2:1; the amount of neopentyl glycol added is 55% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 25% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 10% mol of terephthalic acid, 10% mol of isophthalic acid, 10% mol of terephthalic acid, 10% mol of isophthalic acid, 10% mol of terephthalic acid, 10% mol of 2-methyl-1,3-propanediol and ethylene glycol added; The addition amount of trimethylolpropane is 1%mol of the total addition amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane; the addition amount of trimethyl phosphate is 0.4wt% of the total addition amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane.

[0111] The final polyester for powder coating has a number average molecular weight of 4758 g / mol, an intrinsic viscosity of 0.134 dL / g, an acid value of 18.2 mKOH / g, a glass transition temperature of 61.1° C., and is clear and transparent.

[0112] Example 3

[0113] A method for preparing polyester for powder coating, the specific steps are as follows:

[0114] (a) feeding;

[0115] First, 2-methyl-1,3-propanediol and a hybrid titanium catalyst (manufacturer: Shanghai Huiyi New Material Technology Co., Ltd., model: HCEO) were uniformly mixed to obtain a premix, and then the reactor was preheated to 100° C., and ethylene glycol, terephthalic acid, neopentyl glycol, the premix, trimethylolpropane, and trimethyl phosphate were added thereto;

[0116] (b) esterification reaction;

[0117] After nitrogen or inert gas is introduced to remove the impurity air in the kettle, the temperature in the kettle is raised to 190°C, and the pressure is maintained at 0.1MPa for 3.5h. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 100°C, and the temperature in the kettle is gradually raised to 250°C at a rate of 4°C / 10min;

[0118] The esterification rate of the esterification reaction was 99.5%;

[0119] (c) acid hydrolysis reaction;

[0120] After the temperature in the kettle was lowered to 225°C, isophthalic acid was added and reacted for 60 minutes;

[0121] (d) pre-polycondensation reaction;

[0122] Within 20 minutes, the temperature in the kettle was raised to 240°C and the pressure in the kettle was reduced to -101KPa;

[0123] (e) introducing nitrogen or an inert gas to lower the temperature in the autoclave, and cooling the discharged material to obtain polyester for powder coating;

[0124] In steps (a) to (e), the mass of titanium element in the hybrid titanium catalyst is 150 ppm of the theoretical mass of polyester for powder coating; the alcohol-acid ratio of the reaction system is 1.1:1; the amount of neopentyl glycol added is 60% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 20% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 10% mol of terephthalic acid, The total amount of isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added is 3% mol; the amount of trimethylolpropane added is 2% mol of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added; the amount of trimethyl phosphate added is 0.5wt% of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added.

[0125] The final polyester for powder coating has a number average molecular weight of 4800 g / mol, an intrinsic viscosity of 0.14 dL / g, an acid value of 20 mKOH / g, a glass transition temperature of 62° C., and is clear and transparent.

[0126] Comparative Example 1

[0127] A method for preparing polyester, which is different from Example 3 only in that the hybrid titanium catalyst is completely replaced by TBOT, and the mass of the titanium element in TBOT is the same as that in Example 3.

[0128] The esterification rate of the esterification reaction was 92%; the polyester finally obtained was white and opaque.

[0129] Compared with Example 3, the esterification rate of the esterification reaction in Comparative Example 1 is significantly reduced, and the transparency of the polyester is significantly deteriorated. This is because the catalytic efficiency of the TBOT used in Comparative Example 1 is low under normal pressure (0.1 MPa), resulting in a decrease in the esterification rate of the esterification reaction; at the same time, TBOT is easily hydrolyzed to generate white titanium dioxide particles, which will be dispersed in the polyester system, resulting in the deterioration of the transparency of the polyester.

[0130] Comparative Example 2

[0131] A method for preparing polyester, which is different from Example 3 only in that the hybrid titanium catalyst is completely replaced by tetraisopropyl titanate, and the mass of the titanium element in the tetraisopropyl titanate is the same as that in Example 3.

[0132] The esterification rate of the esterification reaction was 50%; the polyester finally obtained was white and opaque.

[0133] Compared with Example 3, the esterification rate of the esterification reaction in Comparative Example 2 is significantly reduced, and the transparency of the polyester is significantly deteriorated. This is because the catalytic efficiency of tetraisopropyl titanate used in Comparative Example 2 is low under normal pressure (0.1 MPa), resulting in a decrease in the esterification rate of the esterification reaction; at the same time, tetraisopropyl titanate is easily hydrolyzed to generate white titanium dioxide particles, which will be dispersed in the polyester system, resulting in the deterioration of the transparency of the polyester.

[0134] Example 4

[0135] A method for preparing polyester for powder coating, the specific steps are as follows:

[0136] (a) feeding;

[0137] First, 2-methyl-1,3-propanediol and a hybrid titanium catalyst (manufacturer: Shanghai Huiyi New Material Technology Co., Ltd., model: HCEO) were uniformly mixed to obtain a premix, and then the reactor was preheated to 100° C., and ethylene glycol, terephthalic acid, neopentyl glycol, the premix, trimethylolpropane, and trimethyl phosphate were added thereto;

[0138] (b) esterification reaction;

[0139] After nitrogen or inert gas is introduced to remove the impurity air in the kettle, the temperature in the kettle is raised to 190°C, and the pressure is maintained at 0.1MPa for 3.8h. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 105°C, and the temperature in the kettle is gradually raised to 245°C at a rate of 4°C / 10min;

[0140] The esterification rate of the esterification reaction was 99%;

[0141] (c) acid hydrolysis reaction;

[0142] After the temperature in the kettle was lowered to 220°C, isophthalic acid was added and reacted for 60 minutes;

[0143] (d) pre-polycondensation reaction;

[0144] Within 25 minutes, the temperature in the kettle was raised to 220°C and the pressure in the kettle was reduced to -101KPa;

[0145] (e) introducing nitrogen or an inert gas to lower the temperature in the autoclave, and cooling the discharged material to obtain polyester for powder coating;

[0146] In steps (a) to (e), the mass of titanium element in the hybrid titanium catalyst is 170 ppm of the theoretical mass of polyester for powder coating; the alcohol-acid ratio of the reaction system is 1.15:1; the amount of neopentyl glycol added is 60% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 20% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 10% mol of terephthalic acid, The total amount of isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added is 3% mol; the amount of trimethylolpropane added is 1.5% mol of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added; the amount of trimethyl phosphate added is 0.5wt% of the total amount of terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol and trimethylolpropane added.

[0147] The final polyester for powder coating has a number average molecular weight of 4753 g / mol, an intrinsic viscosity of 0.137 dL / g, an acid value of 18.7 mKOH / g, a glass transition temperature of 61.8° C., and is clear and transparent.

Claims

1. A method for preparing polyester for powder coating, wherein the raw materials are subjected to esterification reaction, acidolysis reaction and pre-polycondensation reaction in sequence under the action of a catalyst, wherein the esterification rate of the esterification reaction is 97-99.5%, characterized in that: The pressure of the esterification reaction is 0.1 MPa, the time of the esterification reaction is 3.5-4.4 h, and the catalyst is a hybrid titanium catalyst with the following structural formula: ; The mass of titanium element in the hybrid titanium catalyst is 100-170 ppm of the theoretical mass of polyester for powder coating.

2. The method for preparing a polyester for powder coating according to claim 1, characterized in that: The reaction raw materials include terephthalic acid, isophthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, ethylene glycol, and trimethylolpropane.

3. The method for preparing a polyester for powder coating according to claim 2, characterized in that: The alcohol-acid ratio of the reaction system is 1.1-1.2:1; the amount of neopentyl glycol added is 50-60% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of 2-methyl-1,3-propanediol added is 20-30% mol of the total amount of neopentyl glycol, 2-methyl-1,3-propanediol and ethylene glycol added; the amount of isophthalic acid added is 2-3% mol of the total amount of reaction raw materials added; and the amount of trimethylolpropane added is 1-2% mol of the total amount of reaction raw materials added.

4. The method for preparing a polyester for powder coating according to claim 3, characterized in that: The reaction system also contains a stabilizer, and the amount of the stabilizer added is 0.3-0.5wt% of the total amount of the reaction raw materials added.

5. The method for preparing a polyester for powder coating according to claim 4, characterized in that: The specific steps are as follows: (a) feeding; After preheating the reaction kettle, ethylene glycol, terephthalic acid, neopentyl glycol, 2-methyl-1,3-propanediol, trimethylolpropane, a hybrid titanium catalyst, and a stabilizer are added thereto; (b) esterification reaction; After nitrogen or inert gas is introduced to remove the impurities and air in the kettle, the temperature in the kettle is raised to 190-200°C and the reaction is started. During this process, the oil temperature is adjusted to maintain the top temperature of the esterification tower at 95-105°C, and the temperature in the kettle is gradually raised to 245-260°C at a rate of 4°C / 10min; (c) acid hydrolysis reaction; After the temperature in the kettle is lowered to 220-230°C, isophthalic acid is added and reacted for 60-90 minutes; (d) pre-polycondensation reaction; Raise the temperature in the kettle to 220-250°C within 20-30 minutes and reduce the pressure in the kettle to -101KPa; (e) After nitrogen or inert gas is introduced to lower the temperature in the autoclave, the discharged material is cooled to obtain polyester for powder coating.

6. The method for preparing a polyester for powder coating according to claim 5, characterized in that: In step (a), the preheating temperature is 80-100° C. Before adding the materials, 2-methyl-1,3-propanediol and the hybrid titanium catalyst are first mixed evenly.

7. The method for preparing a polyester for powder coating according to claim 1, characterized in that: The polyester for powder coating has a number average molecular weight of 4000-4800 g / mol, an intrinsic viscosity of 0.13-0.14 dL / g, an acid value of 18-20 mKOH / g, a glass transition temperature of 60-62° C., and is clear and transparent.

Citation Information

Patent Citations

  • A polyester resin resistant to high humidity, heat, and radiation, its preparation method, and its application.

    CN109054004B

  • Polyester resin with high acid value and low acid value for environment-friendly dry blended low-gloss powder coating and preparation method thereof

    CN101445591A

  • Micro / nano-scale sheet type titanium polyester catalyst and application thereof

    CN103059284A

  • Organic titanium compound and composite and preparation methods thereof

    CN103087089A